A review on mechanical properties of FRP bars subjected to seawater sea sand concrete environmental effects. (15th October 2022) - Guo, Xiangke; Xiong, Chuansheng; Jin, Zuquan; Pang, Bo
Abstract: The FRP-reinforced seawater sea sand concrete (FRP-SWSC) utilizes a chloride corrosion-free FRP bars and opens a new avenue for concrete production with the direct employment of locally original sea sand and seawater, which can offer compelling environmental and economic advantages. Herein, a comprehensive review of experimental studies investigating the mechanical properties of FRP bars subjected to SWSC environmental effects, including solution immersion, concrete wrapping, load and solution coupling, and field environment is presented. The residual mechanical strengths of the collected FRP bars, including tensile, interlaminar shear, transverse shear, flexural, and bond strengths, were presented and compared. The deterioration mechanism of FRP bars in SWSC environment induced corrosion was introduced. Durability improvement measures of FRP-SWSC were put forward: (i) using supplementary cementitious materials (SCMs) to reduce the alkalinity and permeability of SWSC and (ii) replacing the partly basalt/glass fiber with carbon fiber to form hybrid-FRP bars. According to the findings from this work, recommendations for prospective works were proposed. Moreover, this review is also expected to provide a comprehensive understanding of the durability of FRP bars in SWSC environments and offer a solid foundation for future research. Highlights: The mechanical properties of FRP-bar subjected to SWSC environmental effects are reviewed. Effects of al mechanical properties and durability of FRP bars are studied. Durability improvement measures of FRP-SWSC were put forward.